Charged-particle multiplicity in proton-proton collisions - Große-Oetringhaus, Jan Fiete; Reygers, Klaus (Journal of physics. G, Nuclear and particle physics, 2010)
This review summarizes and critically reviews measurements of charged-particle multiplicity distributions and pseudorapidity densities in collisions between and . Related theoretical concepts are briefly introduced. Moments of multiplicity distributions are presented as a function of . Feynman scaling, KNO scaling as well as the description of multiplicity distributions with a single negative binomial distribution and with combinations of two or more negative binomial distributions is discussed. Moreover, similarities between the energy dependence of charged-particle multiplicities in and e+e− collisions are studied. Finally, various predictions for pseudorapidity densities, average multiplicities in full phase space and multiplicity distributions of charged particles in collisions at the LHC energies of and 14 TeV are summarized and compared.